Richard B. Donovan, The liturgical drama in Spain. Pontifical Institute of Medieval Studies, Toronto, 1958; vi + 230 pp. - Weber de Kurlat, Frida (El Colegio de México, 1962)
Se reseñó el libro: The liturgical drama in Spain.